2010
DOI: 10.3389/fnint.2010.00005
|View full text |Cite
|
Sign up to set email alerts
|

Following gaze: gaze-following behavior as a window into social cognition

Abstract: In general, individuals look where they attend and next intend to act. Many animals, including our own species, use observed gaze as a deictic (“pointing”) cue to guide behavior. Among humans, these responses are reflexive and pervasive: they arise within a fraction of a second, act independently of task relevance, and appear to undergird our initial development of language and theory of mind. Human and nonhuman animals appear to share basic gaze-following behaviors, suggesting the foundations of human social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
239
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(255 citation statements)
references
References 200 publications
(242 reference statements)
12
239
0
4
Order By: Relevance
“…One neuroimaging study suggested human TPJ may be homologous with the posterior STS in monkeys, based on patterns of resting-state connectivity measured using fMRI. Identifying where others are looking appears to be accomplished by neurons along the STS [100] and in the amygdala [101] that respond to the sight of another individual looking in a particular direction. Inactivation of neurons in the STS using a drug to block neuronal spiking impairs gaze-following in rhesus macaques, consistent with a role in identifying the locus of other animals' attention [102].…”
Section: Cognitive and Neural Boundaries Of Cooperationmentioning
confidence: 99%
“…One neuroimaging study suggested human TPJ may be homologous with the posterior STS in monkeys, based on patterns of resting-state connectivity measured using fMRI. Identifying where others are looking appears to be accomplished by neurons along the STS [100] and in the amygdala [101] that respond to the sight of another individual looking in a particular direction. Inactivation of neurons in the STS using a drug to block neuronal spiking impairs gaze-following in rhesus macaques, consistent with a role in identifying the locus of other animals' attention [102].…”
Section: Cognitive and Neural Boundaries Of Cooperationmentioning
confidence: 99%
“…Certainly further work is required to establish the case for mirror neurons in areas responsible for the control of attention and eye movements. The suggestion that processing eye-gaze direction and wider social orienting mechanisms could occur via mirroring or direct mapping processes has, however, attracted growing interest (Frischen, Loach, & Tipper, 2009;Rizzolatti & Sinigaglia, 2010;Shepherd, 2010). One recent fMRI study has already identified mirror neuron areas which may be responsive to averted and direct gaze in humans (Coudé et al, 2016).…”
Section: The Neural Basis Of Attention To Actionmentioning
confidence: 99%
“…Social attention is an essential ability for obtaining an empathic contact with others and to discover potentially relevant information in the environment [3].…”
Section: Introductionmentioning
confidence: 99%